Distinguishing Brands of A-4 Paper Through Elemental Analysis Using Laser-Induced Breakdown Spectroscopy and Principal Component Analysis - Arbi, Ines; Yürekli, Yunus; Özen, Hülya (Journal of Engineering Technology and Applied Sciences, 2024)
In the realm of forensic science and materials analysis, understanding the composition and characteristics of everyday materials can unveil a plethora of information. This study leverages the precision and efficiency of Laser-Induced Plasma Spectroscopy (LIBS) to dive deep into the elemental makeup of A-4 paper across different brands, offering applications beyond academic research. The results can offer a valuable reference in forensic investigations where distinguishing between paper types could provide key evidence in document authentication or fraud cases. Furthermore, the method provides insights for quality control in paper manufacturing by identifying unique elemental markers that can verify the origin and consistency of paper products. This innovative research employed the ECCO®² brand Laser-Induced Breakdown Spectroscopy (LIBS) device, a state-of-the-art spectrometric system. The device was used to analyze samples from seven distinct A4 paper brands: Mopak®, Office International Copier Bond®, Double A®, Excellent Copy Paper®, Gold®, Master®, and Vera®. Controlled via a computer system and specialized ECCO®² software, the ECCO®² facilitated a comprehensive elemental analysis of these paper samples, focusing on the presence of specific inorganic materials such as glass, inks, and toners that hold forensic value. The study meticulously selected 11 elements (K, Sr, Si, Na, Ba, Mg, Ca, C, Al, Fe, and Ti) for elemental data analysis, based on their relevance and potential to reveal the composition and source of the materials. These elements were chosen due to their prevalence in common additives, fillers, and bleaching agents used in paper manufacturing, making them effective markers for differentiating paper brands based on elemental composition. The LIBS technique, a non-contact and rapid analytical method, allowed for the precise detection of these elements without the need for sample preparation, showcasing its practicality in forensic and analytical applications. Through Principal Component Analysis (PCA), 76.65% discrimination was initially achieved among the A4 paper samples. Notably, when three elements (Al, Fe, and Ti) were excluded, discrimination increased to 83.78%. Further analyses using Principal Component Analysis (PCA) on peak height and peak area data from A4 paper samples yielded discrimination rates of 80.916% and 85.947%, respectively. In this context, peak height refers to the maximum intensity of each elemental emission line, while peak area represents the integrated area under each spectral peak. These distinct spectral metrics capture different aspects of the elemental composition of A4 paper samples, enhancing PCA’s ability to effectively distinguish between paper brands. Finally, when PCA was performed using six elemental pairs identified by the ECCO®² device as optimal for A4 paper differentiation, the discrimination rate reached 97.313%, with variation values calculated at approximately 80%. These results underscore the LIBS method’s reliability and precision in distinguishing different paper types, affirming its valuable application for forensic and quality control purposes.